Genetic diversity in early-maturing soybean genotypes based on biometric and molecular parameters - Bizari, Eduardo H. [UNESP]; Unêda-Trevisoli, Sandra H. [UNESP]; Vianna, Viviane F. [UNESP]; Meyer, Andréia S. [UNESP]; Di Mauro, Antonio O. [UNESP] (My University, 2014)
The objective of this study was to analyze the genetic diversity of 50 early-maturing soybean genotypes, destined for rotation with sugarcane, based on biometric and molecular data, as well as to verify the congruence between groups for different parameters evaluated (phenotypic and molecular). The general Mahalanobis distance was used for both analyses and the UPGMA method for the grouping. The biometric traits were obtained from a random block trial with three replications, evaluated for the following agronomic traits: days for flowering (NDF), days for maturity (NDM), plant height at maturity (PHM), first pod insertion height (FPI), lodging (L), agronomic value (AV), number of pods (NP), grain yield (GY) and oil content (OC). The dissimilarity index varied from 1.52 to 8.88, with a mean of 4.61, with the smallest distance observed for treatments 43 and 13 and the greatest distance for treatments 24 and 70. The genotypes were separated into five groups and according to Singh's criterion, the characters which most contributed to the genetic divergence were number of days to flowering, lodging and plant height at maturity. Ninety-five microsatellite markers were used for the molecular data, of which 75 showed polymorphism between the genotypes evaluated. With the data of the polymorphic molecular markers, 173 alleles were identified with a mean of 2.30 per locus. The group of 75 polymorphic SSR markers managed to distinguish the genotypes, including lines derived from the same cross. The value calculated for the polymorphic information content (PIC) varied from 0.04 to 0.75 with a mean of 0.44. The genetic dissimilarity calculated between the 50 genotypes from the dissimilarity matrix of the molecular data, varied from 0.06 to 0.67 with a mean of 0.44. The smallest distance was observed between treatments 68 and 8 and the greatest distance between treatments 4 and 36. The genotypes were separated into groups based on the genetic distances. According to the biometric and molecular analyses, a significant genetic variability was observed between genotypes. The groups obtained for the molecular and biometric data did not show congruence. Based on this information, it was possible to suggest crossings between divergent genotypes with complementary agronomical traits, where such genotypes could make up future crosses within a genetic improvement program aimed at early-maturation, grain yield and high oil content.
Keywords: Agronomic characters; Glycine max; Molecular marker SSR; Multivariate analysis